Kulit Kacang Tanah (Arachis hypogaea L.) sebagai Adsorben Ion Pb(II) - Oktasari, Ade (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2018)
An experiment on Pb (II) metal ion adsorption using peanut (Arachis hypogea L.) shell without activation (KK), acid-activated (KKA), and base-activated (KKB) has been conducted. Peanut shell powder was activated using H3PO4 and KOH to improve adsorption effectivity and capacity. Characterization results using FT-IR spectrophotometer showed peak at 3410 and 2901 cm-1 indicated OH dan CH aliphatic from framework of cellulose. Optimum condition of Pb(II) adsorption for KK, KKA and KKB was occurred at the same optimum pH, that was pH 5, with contact time 60, 90 and 70 min, respectively. The adsorption kinetic parameter of Pb(II) ion for KK, KKA, and KKB followed pseudo second order kinetic with rate constants (k) in order of 12.279, 4.149, and 32.258 g mmol-1 min-1, with maximum adsorption capacity based on Langmuir isotherm model of 0.598, 0.505, and 0.622 mmol g-1, and adsorption energy of 26.735, 25.789, and 29.245 kJ mol-1, respectively. The results indicated that KOH-activated peanut (Arachis hypogea L.) shell has good adsorption affinity for Pb(II) with highest adsorption capacity compare to those from non-activated and acid-activated.